The influence of body temperature on tissue stiffness, blood perfusion, and water diffusion in the mouse brain - Bertalan, Gergely; Boehm-Sturm, Philipp; Schreyer, Stefanie; Morr, Anna-Sophie; Steiner, Barbara; Tzschaetzsch, Heiko; Braun, Juergen; Guo, Jing; Sack, Ingolf (Acta Biomaterialia, 2019)
While hypothermia of the brain is used to reduce neuronal damage in patients with conditions such as traumatic brain injury or stroke, little is known about how temperature affects the biophysical properties of in vivo brain tissue. Therefore, we measured shear wave speed (SWS), apparent diffusion coefficient (ADC), and cerebral blood flow (CBF) in the mouse brain at different body temperatures to investigate the relationship between temperature and tissue stiffness, water diffusion, and blood perfusion in the living brain. Multifrequency magnetic resonance elastography (MRE), diffusion-weighted imaging (DWI), and arterial spin labeling (ASL) were performed in seven mice while increasing and recording body temperature from hypothermia (28–30 °C) to normothermia (36–38 °C). SWS, ADC, and CBF were analyzed in regions of whole brain, cortex, hippocampus, and diencephalon. Our results show that SWS decreases while ADC and CBF increase from hypothermia to normothermia (whole brain SWS: −6.2%, ADC: +34.0%, CBF: +80.2%; cortex SWS: −10.1%, ADC: +30.9%, CBF: +82.4%; all p > 0.05). We found a significant inverse correlation between SWS and both ADC and CBF in all analyzed regions except diencephalon (whole brain SWS-ADC: r = −0.8, p < 0.005; SWS-CBF: r = −0.84, p < 0.005; cortex SWS-ADC: r = −0.74, p < 0.05; SWS-CBF: r = −0.65, p < 0.05). These results show that in vivo brain stiffness is inversely correlated with temperature, extracellular water mobility, and microvascular blood flow. Regional differences indicate that cortical areas are more markedly affected by hypothermia than central regions such as diencephalon. Temperature should be considered as a confounder in elastographic measurements, especially in preclinical settings. Statement of Significance: Hibernating mammals lower their body temperature and metabolic activity. A hypothermic state can also be induced for medical purposes to reduce the risk of neural damage in patients with neurological disease or injury. However, little is known how physical soft-tissue properties of the in-vivo brain such as water diffusion, blood perfusion or mechanical parameters correlate with each other when temperature changes. Our study demonstrates for the first time that those quantitative imaging markers are tightly linked to changes in body temperature. While water diffusion and blood perfusion are reduced during hypothermia, brain stiffness significantly increases, suggesting that multiparametric quantitative MRI should be used for the noninvasive assessment of brain metabolic activity.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Brain stiffness; Diffusion; Hypothermia; Mouse; Multifrequency MRE; Perfusion; Temperature; Tomoelastography